2018
DOI: 10.1002/elps.201700481
|View full text |Cite
|
Sign up to set email alerts
|

Research advances based on mass spectrometry for profiling of triacylglycerols in oils and fats and their applications

Abstract: Vegetable oils and animal fats are dietary source of lipids that play critical and multiple roles in biological function. Triacylglycerols (TAGs) are the principal component of oils and fats with significant difference in profile among different oils and fats. TAG profiling is essential for nutritional evaluation, quality control and assurance of safety in oils and fats. However, analysis of TAGs is a challenging task because of the complicated composition of TAGs and their similar physicochemical properties i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…The fatty acid profile mainly consisted of monounsaturated fatty acids (MUFA), predominantly oleic acid (C18:1 n‐9) and palmitoleic acid (C16:1 n‐7) acids, along with substantial proportions of the saturated palmitic acid (C16:0) and stearic acid (C18:0). In general, fatty acid percentages decreased in the order of monounsaturated > saturated > polyunsaturated (MUFA > SFA > PUFA), consistent with a previous report (Xu et al., 2018). There was no difference in FA composition between raw and roasted nuts, but that did not necessarily mean there were no differences in the TAG or FFA profiles.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The fatty acid profile mainly consisted of monounsaturated fatty acids (MUFA), predominantly oleic acid (C18:1 n‐9) and palmitoleic acid (C16:1 n‐7) acids, along with substantial proportions of the saturated palmitic acid (C16:0) and stearic acid (C18:0). In general, fatty acid percentages decreased in the order of monounsaturated > saturated > polyunsaturated (MUFA > SFA > PUFA), consistent with a previous report (Xu et al., 2018). There was no difference in FA composition between raw and roasted nuts, but that did not necessarily mean there were no differences in the TAG or FFA profiles.…”
Section: Resultssupporting
confidence: 92%
“…After centrifugation at 8,983 g for 20 min, the oil was transferred to a brown glass container, kept at 4℃, and analyzed within 1 week. A standard procedure with KOH/methanol solution (0.4 mol/L) was used to prepare fatty acid methyl esters (FAMEs) from the oil (Xie et al., 2019; Xu et al., 2018). The FAMEs were analyzed by gas chromatography (Agilent Technologies 7890A, Santa Clara, CA) coupled with a capillary column (HP‐FFAP, 30 m × 0.25 mm × 0.25 μm, Agilent) and a flame ionization detector (FID).…”
Section: Methodsmentioning
confidence: 99%
“…This fact imposes a drawback to assessing acyl position. Indeed, TAG analysis through [M + H] + ions has been shown to be better suited for an APCI source [ 7 , 13 , 26 , 27 ]. Consequently, taking into account previous work by other authors [ 11 , 12 , 26 , 28 , 29 ], we assayed different chromatographic methods for TAG separation, and we found that the method that better fitted our purpose was that in which non-aqueous solvents (i.e., acetonitrile and 2-propanol) with a reverse phase column were used.…”
Section: Discussionmentioning
confidence: 99%
“…50 These studies should be consulted if someone would like to adopt RPLC for analysis of TG species. An extensive list of applications with this and other LC−MS techniques can be found in a recent review by Wei et al 51 2.2. Argentation (Silver Ion) LC−MS for TG Analysis.…”
Section: Introductionmentioning
confidence: 99%